Damage detection in concrete using surface mounted PZT transducers. (2020) - Narayanan, Arun; Kocherla, Amarteja; Subramaniam, Kolluru V.L.
Abstract: Early damage detection in concrete structures is of vital importance since its improve the safety and ensures durability of the structure. In this study, an actuator-receiver (AR) mode of the surface mounted Lead Zirconate Titanate (PZT) transducers is implemented to monitor the stress induced localized damage in a concrete structure. The crack is induced in a notched beam in a controlled manner. The extent and width of the crack are measured using full-field image analysis technique. The received stress waves from the AR pair is analyzed in coherent and diffuse field methods. The coherent field of the received stress wave was analyzed in time and frequency domain while the diffuse filed was analyzed using time-frequency analysis. Delay in the arrival time of maximum energy of the received stress wave is computed using time-frequency analysis of the time-normalized stress wave and is observed to be sensitive to increase in depth of the crack. It is also shown that the attenuation factor (frequency domain) which is derived from the coherent part of the received stress wave is very sensitive to change in crack depth while the change in time of flight (time domain) is least sensitive.